Allergic Responses Induced by a Fungal Biopesticide Metarhizium anisopliae and House Dust Mite Are Compared in a Mouse Model - Marsha D. W. Ward; Yong Joo Chung; Lisa B. Copeland; Donald L. Doerfler (Journal of Toxicology)
Biopesticides can be effective in controlling their target pest. However, research regarding allergenicity and asthma development is limited. We compared the ability of fungal biopesticide Metarhizium anisopliae (MACA) and house dust mite (HDM) extracts to induce allergic responses in BALB/c mice. The extracts were administered by intratracheal aspiration at doubling doses (2.5–80 𝜇g protein) 4X over a four-week period. Three days after the last exposure, serum and bronchoalveolar lavage fluid (BALF) were collected. The extracts' relative allergenicity was evaluated based on response robustness (lowest significant dose response compared to control (0 𝜇g)). MACA induced a more robust serum total IgE response than HDM. However, in the antigen-specific IgE assay, a similar dose of both MACA and HDM was required to achieve the same response level. Our data suggest a threshold dose of MACA for allergy induction and that M. anisopliae may be similar to HDM in allergy induction potential.